2002
DOI: 10.1093/ps/81.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and the Enhancement of Immune Responses in Immature Male Chickens

Abstract: Understanding the role of melatonin in affecting different physiological functions, especially immune responses, is becoming increasingly important in the basic and applied sciences. Enhancing the immune response will result in increasing disease resistance and, therefore, improve production efficiency. The purpose of the present study was to investigate the effects of melatonin, administered during the light or dark period, on BW, feed consumption (FC), and immune responses of immature chickens. Eight-week-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 21 publications
0
22
1
1
Order By: Relevance
“…It was reported that under stressful heat conditions, melatonin application improved the feeding efficiency of Japanese quail and reduced their oxidative stress47. Moreover, melatonin could enhance immunity in chickens against disease144849. As a result, these activities of melatonin may also help the hens preserve their egg-laying rate after their egg-laying peak age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that under stressful heat conditions, melatonin application improved the feeding efficiency of Japanese quail and reduced their oxidative stress47. Moreover, melatonin could enhance immunity in chickens against disease144849. As a result, these activities of melatonin may also help the hens preserve their egg-laying rate after their egg-laying peak age.…”
Section: Discussionmentioning
confidence: 99%
“…In birds, melatonin also functions as an immunoenhancement agent12. Its supplementation elevated cellular and humoral immune responses in Japanese quail13 and chicken141516. The signalling pathway analysis showed that both cellular and humoral immunoresponses triggered by melatonin were exclusively mediated by its receptor subtype MT2 (Mel 1b)17.…”
mentioning
confidence: 99%
“…Melatonin enhances in vitro production of interleukins and interferons by circulating human CD4 þ cells [53]. The number of white blood cells of chickens injected with melatonin was significantly higher than that of saline-injected birds [54]. Melatonin should not be considered a miracle drug, but it does have immunomodulatory effects that might have clinical relevance [55].…”
mentioning
confidence: 99%
“…Особенно существенна роль мелатонина как иммуномодулятора при нарушениях иммунологического статуса, вызванных снижением эндогенного уровня гормона при функциональных и фармакологических воздействиях (Srinivasan et al, 2005;Moore et al, 2002). Уровень мелатонина положительно коррелирует как с гуморальным (Akbulut et al, 2001), так и с клеточным иммунитетом (Brennan et al, 2002;Champney et al, 1997). Введение экзогенного мелатонина в периоды, когда наблюдается снижение активности пинеальной железы (Nelson, Drazen, 1999;Haldar et al, 2001), приводит к усилению отдельных показателей иммунитета.…”
Section: Discussionunclassified